3ds max 6 discreet advanced courseware: - Maffei, Ken (Autodesk, 2003)
This courseware module introduces you to MAXScript, the scripting language built into 3ds max. This module covers the creation of objects with MAXScript, arrays, collections, control structures, the construction of UI elements, creation of parametric objects, and a variety of additional topics